Modulation of intraocular pressure by unilateral and forced unilateral nostril breathing in young healthy human subjects - Mohan, Satagopam Mitti; Reddy, Sagili Chandrasekhara; Wei, Lee Yoong (Springer Science and Business Media LLC, 2001)
Purpose: To determine the effects of unilateral right/left nostril breathing (URNB/ULNB) and forced unilateral right/left nostril breathing (FURNB/FULNB) on intraocular pressure (IOP) and to examine the differences in the IOP during the various phases of nasal cycle. Methods: Young healthy volunteers of either sex aged between 19-24 years, participated in the sessions using URNB/ULNB (n = 52) and FURNB/FULNB (n = 28). The nostril dominance was calculated from signals recorded on the PowerLab equipment, representing pressure changes at the end of the nostrils during respiration. The IOP was measured with Tono-Pen. The subjects were divided into 4 groups viz. right nostril dominant (RND), left nostril dominant (LND), transitional right nostril dominant (TRND) and transitional left nostril dominant (TLND) groups. The IOP data 'before and after' URNB/ULNB or FURNB/FULNB were compared by using paired t-test. The baseline data of IOP between the groups were analysed by using independent samples t-test. Results: The URNB decreased the IOP in the LND and TLND (p < 0.01) and also in the RND (p < 0.05) groups but not significantly in the TRND group. The ULNB decreased the IOP in the RND group (p < 0.01) only. The FURNB significantly reduced the IOP (p < 0.05) only in the LND and RND groups. The FULNB decreased the IOP but not significantly. The baseline IOP did not differ significantly between the LND, RND, TLND and TRND groups. Conclusion: The URNB/FURNB reduced the IOP, while ULNB/FULNB failed to increase the IOP significantly. It is suggested that the lowering of IOP by URNB indicated sympathetic stimulation.